2020
DOI: 10.1186/s12978-020-00964-1
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and covert family planning users’ experiences self-injecting contraception in Uganda and Malawi: implications for waste disposal of subcutaneous depot medroxyprogesterone acetate

Abstract: Background: Self-administered subcutaneous depot medroxyprogesterone acetate (DMPA-SC) is poised to increase access to contraception; however, governments are concerned about the waste management of used units. Selfinjectors in Malawi and Uganda are currently instructed to store used units in containers and return them to health workers for disposal. However, this may not be feasible in low-resource settings, especially for younger or covert self-injectors. We describe adolescent (15-19 years) and adult (20-49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 32 publications
(46 reference statements)
0
31
1
Order By: Relevance
“…Burke et al. make the case through qualitative inquiry that adolescents prefer individual over group training; however, our quantitative results did not reveal significant differences in their preferences [ 16 ]. Indeed, a sizable share desired group training.…”
Section: Discussioncontrasting
confidence: 55%
“…Burke et al. make the case through qualitative inquiry that adolescents prefer individual over group training; however, our quantitative results did not reveal significant differences in their preferences [ 16 ]. Indeed, a sizable share desired group training.…”
Section: Discussioncontrasting
confidence: 55%
“…To date, qualitative research on motivators and barriers to self-injection has been limited. In Malawi and Uganda, Burke and colleagues explored barriers to DMPA-SC use for adolescents and/or covert users of contraception, where the authors hypothesised that disposal of the product after self-injection may pose substantial hindrance to continued use and found that indeed disposal placed increased risk and stress on self-injectors, specifically for those attempting to use covertly 38. Therefore, not only storage and usage should be considered when attempting to use this method covertly, but also safe disposal ramifications.…”
Section: Most Women Prefer Injectable Contraceptives To Be Provider A...mentioning
confidence: 99%
“…These trained qualitative facilitators, including AZ, used semi-structured interview and FGD guides, respective to each participant group, which explored topics such as what participants knew about DMPA-SC and self-injection, personal-and communitylevel views on the methods, why they believed women would or would not choose to self-inject, and how they could support or be supported in DMPA-SC self-injection use (men and female clients). Interview and FGD guides were developed based on several years of experience conducting quantitative and qualitative research about DMPA-SC self-injection in Mangochi district in Malawi [12,15,[26][27][28][29].…”
Section: Data Collectionmentioning
confidence: 99%
“…Self-injection requires fewer clinic visits and, therefore, users may save time and money and may inject themselves in a private location at their convenience. Published literature has also described self-injection as particularly promising for reaching younger women, new users of contraceptive methods, and covert users [ 14 , 15 ]. Based on the feasibility and acceptability of DMPA-SC self-injection, Malawi’s Ministry of Health (MOH) introduced DMPA-SC (both provider-administered and self-injected) country wide to expand the contraceptive method mix [ 16 ].…”
Section: Introductionmentioning
confidence: 99%